2012
DOI: 10.1136/annrheumdis-2012-201456
|View full text |Cite
|
Sign up to set email alerts
|

Very early rheumatoid arthritis as a predictor of remission: a multicentre real life prospective study

Abstract: BackgroundTo assess whether, in the real world of three early arthritis clinics, early referral could allow the best outcome, ie, remission, to be reached, and whether reaching the outcome was more dependent on therapy than on disease duration or vice versa.Methods1795 patients with early arthritis (symptom duration ≤12 months) were entered into a prospective follow-up study. 711 patients (39.6%) were diagnosed with rheumatoid arthritis (RA). Each RA patient was treated according to the local algorithm, in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
79
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 21 publications
14
79
0
4
Order By: Relevance
“…Consistent data were found in previous studies with infliximab, suggesting that the first 2 years of disease may be a valid window of opportunity for effective therapy in RA 28. Another study34 involving 711 patients with early RA diagnosed from over 1795 patients with symptoms of arthritis for less than 12 months showed that patients starting any treatment within 12 months since the onset of first symptoms or receiving disease-modifying agents (DMARDs) within 3 months from disease onset were significantly more likely to achieve disease remission (OR 2.03 (1.25–3.30) and 1.65 (1.06 to 2.55), respectively). The TICORA study35 showed the potential disease-modifying effect of intensive management versus routine care (mean disease duration: 16 months).…”
Section: Introductionsupporting
confidence: 85%
“…Consistent data were found in previous studies with infliximab, suggesting that the first 2 years of disease may be a valid window of opportunity for effective therapy in RA 28. Another study34 involving 711 patients with early RA diagnosed from over 1795 patients with symptoms of arthritis for less than 12 months showed that patients starting any treatment within 12 months since the onset of first symptoms or receiving disease-modifying agents (DMARDs) within 3 months from disease onset were significantly more likely to achieve disease remission (OR 2.03 (1.25–3.30) and 1.65 (1.06 to 2.55), respectively). The TICORA study35 showed the potential disease-modifying effect of intensive management versus routine care (mean disease duration: 16 months).…”
Section: Introductionsupporting
confidence: 85%
“…Five of these eight studies showed a significant association between shorter symptom duration and increased frequency of remission 12 14 17 24. Of the four HQ studies, one study did not observe a significant association with symptom duration,30 two studies found a signification association,17 24 and one study assessed two cohorts of differently treated patients, showing a significant association in one but not in the other patient group 23.…”
Section: Resultsmentioning
confidence: 95%
“…Evidence indicates that early aggressive treatment results in greater improvement than therapy initiated later in rheumatoid arthritis (RA) disease 5 6. It’s very important that GPs could identify patients with suspected RA and refer them to rheumatological experts.…”
mentioning
confidence: 99%